The dual role of Escherichia coli in the course of ulcerative colitis. Issue 1 (December 2016) - Pilarczyk-Zurek, Magdalena; Strus, Magdalena; Adamski, Pawel; Heczko, Piotr
Abstract Background This study examines the dual role ofEscherichia coli in the course of ulcerative colitis (UC). The intestinal microbiota is considered to play an important role in UC pathogenesis, but howE. coli contributes to inflammation in UC is still unknown. On the one hand, we demonstrated that there was a significant increase in the number ofE. coli at the sites of inflammation in patients with UC, which can lead to immune system activation, whilst, on the other hand, E. coli may contribute to the resolution of inflammatory reactions sinceE. coli can inhibit hydroxyl radical formation by eliminating substrates of the Fenton reaction, by assimilating ferrous iron (Fe2+ ) and inducing the decomposition of hydrogen peroxide (H2 O2 ). On this way, E. coli may affect the initiation and/or prolongation of remission stages of UC. Methods TenE. coli strains were isolated from the colonic mucosa of patients in the acute phase of UC. Using PCR, we examined the presence of genes encoding catalases (katG andkatE ) and proteins participating in iron acquisition (feoB, fepA, fhuA, fecA, iroN, fyuA, andiutA ) in theseE. coli strains. To determine if iron ions influence the growth rate ofE. coli and its ability to decompose H2 O2, we grewE. coli in defined culture media without iron (M9(-)) or with ferrous ions (M9(Fe2+ )). Expression levels of genes encoding catalases were examined by real-time PCR. Results All investigatedE. coli strains had catalase genes (katG, katE ), genes coding for receptors for Fe2+ (feoB ) and at least one of the genes responsible for iron acquisition related to siderophores (fepA, fhuA, fecA, iroN, fyuA, iutA ).E. coli cultured in M9(Fe2+ ) grew faster thanE. coli in M9(-). The presence of Fe2+ in the media contributed to the increased rate of H2 O2 decomposition byE. coli and inducedkatG gene expression. Conclusions E. coli eliminates substrates of the Fenton reaction by assimilating Fe2+ and biosynthesizing enzymes that catalyze H2 O2 decomposition. Thus, E. coli can inhibit hydroxyl radical formation, and affects the initiation and/or prolongation of remission stages of UC.